2017
DOI: 10.7448/ias.20.01.21362
|View full text |Cite
|
Sign up to set email alerts
|

Virological response and resistances over 12 months among HIV‐infected children less than two years receiving first‐line lopinavir/ritonavir‐based antiretroviral therapy in Cote d’Ivoire and Burkina Faso: the MONOD ANRS 12206 cohort

Abstract: Introduction: Lopinavir/ritonavir-based antiretroviral therapy (ART) is recommended for all HIV-infected children less than three years. However, little is known about its field implementation and effectiveness in West Africa. We assessed the 12-month response to lopinavir/ritonavir-based antiretroviral therapy in a cohort of West African children treated before the age of two years.Methods: HIV-1-infected, ART-naive except for a prevention of mother-to-child transmission (PMTCT), tuberculosis-free, and less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
5
13
0
Order By: Relevance
“…Our findings starkly contrast the only other report of drug resistance among children failing first-line cART in Ethiopia, undertaken on specimens collected from 13 participants only three years following cART rollout, where only one child harbored HIV-1 drug resistance [ 41 ]. Our findings are comparable to rates of overall drug resistance reported in pediatric first-line treatment failure in other African nations including Cote d’Ivoire and Burkina Faso (75%) [ 38 ], Mali (73%) [ 37 ] and slightly lower than those reported in Cameroon (90%) [ 39 ]. Dual-class resistance was most commonly observed in our cohort (69%), an observation consistent with reports from settings where similar pediatric first-line regimens are currently used (e.g., Mali and Cameroon) [ 37 , 39 , 94 , 95 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings starkly contrast the only other report of drug resistance among children failing first-line cART in Ethiopia, undertaken on specimens collected from 13 participants only three years following cART rollout, where only one child harbored HIV-1 drug resistance [ 41 ]. Our findings are comparable to rates of overall drug resistance reported in pediatric first-line treatment failure in other African nations including Cote d’Ivoire and Burkina Faso (75%) [ 38 ], Mali (73%) [ 37 ] and slightly lower than those reported in Cameroon (90%) [ 39 ]. Dual-class resistance was most commonly observed in our cohort (69%), an observation consistent with reports from settings where similar pediatric first-line regimens are currently used (e.g., Mali and Cameroon) [ 37 , 39 , 94 , 95 ].…”
Section: Discussionsupporting
confidence: 83%
“…As a result, regimens are often changed without knowledge of HIV-1 drug resistance [ 27 , 28 ] and the contribution of drug resistance to treatment failure in these settings remains incompletely understood. Although studies of HIV-infected adults failing first-line cART in Africa [ 29 , 30 , 31 , 32 ], Asia [ 33 , 34 ] and Central America [ 35 ], as well as a meta-analysis across multiple global sites [ 36 ], suggest resistance mutation burden is substantial in these populations, studies investigating the burden of drug resistance among children failing first-line cART in resource limited-settings are scarcer [ 37 , 38 , 39 , 40 ], thus limiting our knowledge in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Various predictors of VF have been identified and reported in the literature, which include younger age [ 30 ], low CD4% at the time of ART initiation [ 30 ], type of ART [ 26 , 30 ], baseline NNRTI resistance [ 26 , 28 ], etc. Father as the main caregiver of the child and lack of access to tap water; have also been identified as risk factors for VF [ 32 ]. Njom et al [ 33 ] reported that being motherless children (motherless orphanhood) was associated with VF (aOR: 2.9, 95% CI 1.3–6.1).…”
Section: Discussionmentioning
confidence: 99%
“…In viral hepatitis, baseline and ontreatment VLs help guide therapeutic decisions [2,[9][10][11]. In the HIV-1-infected patient on combination antiretroviral therapy, a detectable VL signifies active viral replication and can trigger one of several possible interventions [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%